HOW TO USE PEDAGOGICAL TERMS TO DESIGN EXCELLENT LEARNING ENVIRONMENT - Mustafoqulova, Zarifa Baxodir qizi (Educational Research in Universal Sciences, 2022)
This article deals with the pedagogical terms to design excellent learning environment. Learning environment refers to the diverse physical locations, contexts, and cultures in which students learn. Since students may learn in a wide variety of settings, such as outside-of-school locations and outdoor environments, the term is often used as a more accurate or preferred alternative to classroom, which has more limited and traditional connotations—a room with rows of desks and a chalkboard, for example.